Optical visualization of carbon nanotubes-a unifying linkage between microscopic and spectroscopic characterization techniques - Backes, Claudia; Englert, Jan; Bernhard, Nicolas; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Small, 2010)
The optical bright- and dark-field visualization (see image) of single-walled carbon nanotubes spin-casted onto Si/SiO2 substrates with a 300-nm-thick oxide coating is reported. This novel procedure gives access to a low-cost correlation of Raman spectroscopy with microscopic techniques (atomic force microscopy, scanning electron microscopy) greatly facilitating nanotube characterization.